Psychological distress and socio-demographic correlates among old-age home residents in Bengaluru, Karnataka: a cross-sectional study - Sequeira, Sony; Savatagi, Shivannad B.; Lakhani, Sheetal (International Journal Of Community Medicine And Public Health, 2025)
Background: The shifting family structure from joint to nuclear families, migration of young people leaving the elderly behind and increased life expectancy have contributed to the rise of old-age homes. Delivering high-quality care in these settings is challenging, as social isolation can increase the risk of depression, anxiety and stress. Sociodemographic factors such as age, gender, education, previous employment, past living arrangements, having living children and previous locality may impact the mental health of elderly residents in these facilities. Methods: A cross-sectional research design using systematic random sampling included 125 residents from the old age homes. The DASS-21 was used to assess psychological distress, alongside the collection of sociodemographic information. To investigate associations and differences between groups, chi-square tests, t-tests and ANOVA were employed. Results: The participants demonstrated levels of depression ranging from moderate to extremely severe, with 57.6% affected, as well as anxiety at 62.4% and stress at 36.8%. Independent t-tests and one-way ANOVA accompanied by post hoc tests revealed that females, individuals aged 80 and older, those with living children and those who have previously cohabited with their children exhibited notably higher scores of psychological distress. Conclusions: This study highlights high rates of depression, anxiety and stress among elderly individuals in old age homes. Sociodemographic factors such as age, gender and living arrangements significantly influence their mental health. Implementing targeted interventions like regular counselling, recreational activities and guided meditation is essential to address their needs.